Application of Problem-Based Learning Model and Role Play Assisted by Moneybag Media to Improve Financial Literacy of Elementary School Students - Rahayu, Sri; Salsabila, Helmina; Wahyuny, Indra (Actual Insight : Lembaga Penelitian Pengembangan, Penerbitan dan Publikasi, 2025)
Financial literacy is a crucial life skill encompassing knowledge, attitudes, and behaviors related to managing finances wisely. However, the financial literacy level of second-grade students in Class 2A at State Elementary School Kebonsari 3 Malang City remains low. This study aims to enhance students’ financial literacy through the implementation of a Problem-Based Learning model integrated with the Role Play method, supported by the use of Moneybag media in the topic